تاريخ النحو العربي : المذهب البغدادي - Situmorang, Arnika Sarifa; Wahab, Muhbib Abdul (Al-Muyassar: Journal of Arabic Education, 2025)
تطور علم اللغة العربية لا يمكن فصله عن الدور الكبير للمذاهب النحوية، بما في ذلك مذهب بغداد. ظهر هذا المذهب استجابة للحاجة إلى نهج أكثر شمولية ومرونة في فهم القواعد النحوية العربية، خاصة في ظل تطور الثقافة والفكر في العصر العباسي. يتناول البحث خصائص ومساهمات وتأثيرات مذهب بغداد في تاريخ تطور علم اللغة العربية، مما يجعله من الركائز المهمة في التقليد العلمي الإسلامي خلال العصر الذهبي. هذا البحث يستخدم المنهج الكيفي مع المقاربة التاريخية-الوصفية. تم جمع البيانات من خلال دراسة الأدبيات حول أعمال علماء مذهب بغداد، مثل المفصّل للأزماخشرى، وكذلك تحليل النصوص الأولية والثانوية الأخرى. تم إجراء التحليل باستخدام أسلوب التفسير التاريخي لتحديد الخصائص، والمساهمات، والتأثيرات لمذهب بغداد..أظهرت نتائج البحث أن مذهب بغداد يتسم بنهج فريد يجمع بين المبادئ العقلانية لمذهب البصرة والنهج النصي لمذهب الكوفة. يوفر هذا النهج الانتقائي تأثيرًا كبيرًا في تطوير قواعد جديدة تتناسب مع تنوع الثقافة واللغة. كما أن الموقع الجغرافي وبغداد كمركز للحضارة الإسلامية ساهم بشكل كبير في نشر وتطوير علم النحو، مما جعل هذا المذهب نقطة محورية في تاريخ اللغة العربية.الكلمة الأساسية : المذهب البغدادي، علم النحو، المنهج الانتقائي AbstrakThe development of Arabic philology cannot be separated from the significant role of grammatical movements, including the Baghdad movement. This doctrine emerged in response to the need for a more comprehensive and flexible approach to understanding Arabic grammatical rules, especially in light of the development of culture and thought in the Abbasid era. The research addresses the characteristics, contributions, and influences of the Baghdad movement in the history of the development of Arabic philology, making it one of the important pillars of the Islamic scientific tradition during the Golden Age. This research utilizes a qualitative approach with a historical-descriptive approach. Data was collected by studying the literature on the works of Baghdad movement scholars, such as Azmakhshari's Al-Mufasil, as well as analyzing other primary and secondary texts. The analysis was conducted using a historical interpretation method to identify the characteristics, contributions, and influences of the Baghdad movement.The results of the research showed that the Baghdad movement is characterized by a unique approach that combines the rationalist principles of the Basra movement with the textual approach of the Kufa movement. This eclectic approach provides great influence in the development of new rules that suit the diversity of culture and language. The geographical location of Baghdad as a center of Islamic civilization contributed greatly to the spread and development of grammar, making this doctrine a pivotal point in the history of the Arabic language.Keyword: Baghdad movement, ilmu nahwu, eclecticism